Exploratory study on NGO reporting requirements - Stagman,Madelein (University of the Witwatersrand, Johannesburg, 2024)
Non-Government Organisations or Charitable Organisations (COs) are playing increasingly important roles in supporting positive social and environmental change where governments are lacking. Despite this importance, the area is under-researched, and, unlike for-profit companies, there is no standardised reporting framework to guide COs’ external reporting. To begin to address this gap, this study employs an interpretive qualitative approach inspired by grounded theory, utilizing semi-structured, open-ended interviews to gain an understanding of the reporting environment of COs, the users of CO reports, what reporting challenges COs experience and what constitutes useful information for CO users. In doing so, the thesis makes important contributions to both literature and practice. The study finds that there is a need for a standardised reporting framework, emphasising the importance of meeting the diverse information needs of stakeholders, particularly large donors. There is a need for key financial and non-financial information to be reported. For example, interviewees highlighted the need for COs to report on information that speaks to their credibility; their outputs, outcomes and impacts; and what Corporate Social Responsibility initiatives their organisation is well aligned to. These information requirements are not satisfied by traditional financial statements, driving the need for the creation of a tailor- made reporting framework. While not the objective of this study, the thesis makes an additional contribution by providing an example of what such a standardised reporting framework could look like to inspire and accelerate future research in this area.
A research report submitted in fulfillment of the requirements for the Master of Commerce, in the Faculty of Commerce Law and Management, School of Accountancy, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Charitable Organisations; NGOs; external reporting framework; transparency; accountability; SDG-16: Peace, justice and strong institutions; SDG-17: Partnerships for the goals